REPEATED LUNG RESECTIONS IN THE TREATMENT OF POSTOPERATIVE RECURRENT TUBERCULOSIS OF THE PREVIOUSLY RESECTED LUNG - I. B. Murgustov; I. I. Martel; A. A. Glotov; I. I. Enilenis; A. B. Bizhanov; Y. G. Imagozhev; V. V. Koroev; O. S. Kesaev; D. B. Giller (Сеченовский вестник, 2012)
Repeated lung resections in the treatment of postoperative recurrent tuberculosis of the previously resected lung are analyzed in this paper.